Mainstream and specialized foundation-phase teachers' understandings of autism disorders in South Africa - Ribeiro, Dominique Rosa (My University, 2019)
The implementation of the inclusion policies in Education White Paper 6, the ever-increasing prevalence of Autism Spectrum Disorder (ASD) and the reality that many classrooms accommodate undiagnosed students on the spectrum all stress the necessity of comprehensively skilled teachers. Ascertaining teachers’ levels of knowledge regarding ASD in South Africa is thus an integral step towards establishing whether they are adequately equipped to effectively adhere to these policies and is the initial step towards ensuring their competence and ability to assist in improving the outcomes of ASD in South Africa. Using a novel, self-developed measure, the Autism Spectrum Disorder Knowledge Questionnaire (ASD-KQ), 209 foundation-phase teachers from across mainstream and specialized sectors and across the region were surveyed in order to establish the current state of knowledge on ASD in the foundation-phase educational sector in South Africa. Overall, the sample of teachers surveyed scored well (M = 21.7, 73%) and proved themselves adequately knowledgeable on the topic. However, specialized teachers still obtained higher levels of overall knowledge than mainstream teachers. Upon further investigation, increased scores were attributed to the significant influence of gender, educational attainment and the sector in which teachers worked. These results not only serve to suggest that South-African foundation-phase teachers have been adequately equipped with the disorder-specific knowledge integral to beginning to accommodate students on the spectrum, but also serve to encourage further skill development, advise subsequent policy and related resource allocation and provide opportunities for future research on developmental disorders in Sub-Saharan Africa.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Education (Educational Psychology) to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, 2019
Keywords: Autism spectrum disorders--Africa, Sub-Saharan; Autism in children